Math

Simplify by factoring. ^3sqrt 54x^8

1. 👍
2. 👎
3. 👁
1. Your notation is unconventional and unclear.

What is the meaning of the ^ in front of the 3?

Is the square root supposed to be of all of 54 x^8?. Or are you taking the cube root of everything?

The square root of 54x^8 is
sqrt6* 3x^4

1. 👍
2. 👎

Similar Questions

Simplify (2sqrt(5)+3sqrt(7))^2 ~~~ Can you show the steps. I want to learn how to do it now so I won't have to pester y'all again with my feeble algebra questions :3

2. Algebra

What no should be added to 27x^3-54x^2+36 x -11. So that the resulting polynomial. Becomes divisible by (3x-2)

3. Calculus

1) yy'-e^x= 0, and y=4 when x=0 means that: A)y=x-lnx^2+4 B)y^2=4x^2+3 C)y=-2x+1/2x^3 D)y^2=2e^x+14 E)1/2ln|x^2+4|+6 2) The rate of change of P with respect to t is directly proportional to (10-t) and inversely proportional to the

4. Algebra

SHOW ALL WORK 1 what is the solution of the equation sqrt(2x+13)-5=x 2 what is the solution of the equation 3(^5sqrt((x+2)^3))+3=27 3 what is the simplest form of the radical expression 3(^3sqrt(2a)-6(^3sqrt(2a) Thank you :)

1. Calculus

Find the linear approximation of the function f(x)=^3sqrt(1+3x) at a=0 and use it to approximate ^3sqrt(1.03)Is this an overestimate or underestimate of the actual value? Explain your answer in terms of the tangent line and the

2. Algebra

Raise the quantity in parentheses to the indicated exponent and simplify the resulting expression with positive exponents. ((-27x^0 y^(-2))/(54x^(-5) y^(-4) ))^(-2)

3. Algebra II

simplify by factoring ã90 is this correct? ^3ã10

4. math

Find the value of Polynomial 27X2 + 54X - 2 when X = 2

1. Algebra

simplify the cube root of -54x^6y^4 Crt(-54) = -3Crt(2)....(Crt means cube) root Crt(x^6) = x^2 Crt(y^4) = yCrt(y) Now can you put it all together?

2. Simplifying radical expressions

how do you multiply and simplify 3*^3sqrt of 5y^3* 2* ^3sqrt of 50y^4

3. Algebra

Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt[3]+2sqrt[27]-sqrt[12] 3sqrt[3]+2sqrt[3*9]-sqrt[2*6] 3sqrt[3]+3*2sqrt[3]-2sqrt[3] 3sqrt+6sqrt[3]-2sqrt[3] = 7sqrt[3] 2.Simplify

4. calculus

f(t)=3sqrt(2t-1) why domain is all real #'s ? 3sqrt(2t-1) >= 0 ( 3sqrt(2t-1) )^3 >= (0)^3 t>= 1/2 ?